Digital skills in middle and university students. Homogeneous or heterogeneous? (Praxis Educativa, 2020)
Today's work world demands a set of competencies that are key and highly valued, among them, digital skills. Within this framework, the paper presents data about the digital skills of current students. A total of 454 students from different university degrees (engineering, economics and humanities) and from a secondary school participated in the research. They responded to a questionnaire on ICT uses and self-perceptions of their digital competencies for the performance of activities that require the use of technology. The results show different levels of mastery (high, medium and low) with respect to 18 activities consulted. In the same way, 10 of the 18 activities showed differences when groups where compared. Engineering students generallyreported greater mastery. Discussion revolves around highlighting the importance of generating, from academic contexts, opportunities for the development of different digital skills.
Keywords: digital skills; students; middle level; university; self-perceptions